1977
DOI: 10.1021/es60127a007
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric chemistry of N-nitroso dimethylamine

Abstract: Gaseous dimethylamine, (CH3)2NH, reacts in air with gaseous nitrous acid, HONO, to yield N-nitroso dimethylamine, (CH.LNNO. Long path infrared spectroscopy is used to monitor these reactions at concentration levels of partsper-million. The measured reaction rate shows that a small degree of nitrosation of dimethylamine vapor might take place during the night in a heavily polluted urban atmosphere. Nitrosation reactions would essentially cease after sunrise because the nitrous acid would be destroyed by photoly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
65
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(73 citation statements)
references
References 0 publications
8
65
0
Order By: Relevance
“…Most research has focused on nitrosation reactions in solution, but gas phase nitrosation has been reported in simulated outdoor atmospheres (41,42) and in an industrial environment in East Germany (43). It is known that the concentration of NNK in sidestream cigarette smoke is higher than that in mainstream cigarette smoke (7,44).…”
Section: Discussionmentioning
confidence: 99%
“…Most research has focused on nitrosation reactions in solution, but gas phase nitrosation has been reported in simulated outdoor atmospheres (41,42) and in an industrial environment in East Germany (43). It is known that the concentration of NNK in sidestream cigarette smoke is higher than that in mainstream cigarette smoke (7,44).…”
Section: Discussionmentioning
confidence: 99%
“…Combustion often results in the formation of nitrogen-containing species (i.e., NO x or nitroso radicals) that react with species such as dimethylamine to produce nitrosamines. Relatively slow NDMA formation may occur in the atmosphere due to reaction of NO x (principally atmospheric nitrous acid) with dimethylamine released by industrial sources (Hanst et al, 1977;Cohen and Bachman, 1978). However, atmospheric NDMA may accumulate only at night because it degrades quickly by sunlight photolysis (Hanst et al, 1977;Tuazon et al, 1984).…”
Section: Nitrosation: Ndma Formation Via Nitritementioning
confidence: 99%
“…On the basis of those observations, some researchers suggested that NDMA formed in the polluted atmosphere could be responsible for elevated urban cancer rates (Shapley, 1976). However, it was subsequently determined that a factory using dimethylamine was located near Belle, WV, and that air concentrations of NDMA in areas not impacted by industrial processes were orders of magnitude lower than the initial reports (Hanst et al, 1977;Cohen and Bachman, 1978;Fine, 1978).…”
mentioning
confidence: 99%
“…Besides its importance for the atmospheric oxidation potential, HONO is part of acid and nutrient deposition to the biosphere. Moreover, growing concern exists about possible health effects due to the formation of nitrosamines (Hanst et al, 1977;Pitts et al, 1978) where HONO acts as the nitrosating agent, especially in indoor environments after wall reactions of HONO with nicotine (Sleiman et al, 2010). Despite three decades of research since the first unequivocal detection of HONO in the atmosphere (Perner and Platt, 1979), HONO formation processes in the atmosphere are still under discussion, especially during daytime where large discrepancies were found between mixing ratios calculated from known gas phase chemistry and measured daytime mixing ratios .…”
Section: Introductionmentioning
confidence: 99%